The uranium and radon gas concentrations and impact on human health: a case from abandoned gold mine tailings in the West Rand area, Krugersdorp, South Africa. - Moshupya, Paballo Marry (My University, 2019)
The occurrence of uranium and radon gas has long been recognized as a cause of adverse health impacts on the exposed population. The current study was conducted in the Krugersdorp area, West Rand. The area is dominated by abandoned tailings dams from gold and uranium mines, which could be the potential source for toxic metals and gases. In this study, the sampling of rocks, tailings, construction materials and water was carried out for geochemical analyses. For the characterisation of radon, 60 radon monitors were installed in indoor and outdoor environments. The results showed that mine tailings in the area contained high uranium levels, with a maximum of 149.76 ppm and a mean value of 48.87 ppm, which exceptionally exceeds the levels found in underlying rocks. Surface water samples were found to contain uranium levels ranging between 1.93 mg/l and 4.7 mg/l, which are above the safe level of 0.015 mg/l recommended by the World Health Organization. The high uranium concentrations were found to be derived from the residue of adjacent tailings dams. Results show that the radon levels in the area range from 31.7 Bq/m3 to 1068.8 Bq/m3 and thus immensely exceed the typical expected outdoor radon level of about 10 Bq/m3 estimated by the United Nations Scientific Committee on the Effects of Atomic Radiation. Significantly high average values of 187.4 Bq/m3 were obtained from gold tailings dams. The radon levels released from tailings were found to contribute to elevated levels in the natural background. In general, a decrease in radon levels with increasing distance from tailings was noted. In indoor environments, radon concentration ranged up to a maximum of 173.5 Bq/m3, which is above the 100 Bq/m3 recommended by the World Health Organization. The effective doses received by the public showed a maximum of 10.11 mSv/y, which is above the recommended value of 1 mSv/y, and thus have a greater potential to pose a high health risk to the residents. Corroborating the aforementioned statement, a high frequency of deaths that are related to lung cancer were documented in the area and were related to elevated radon levels.
A Research Report submitted to the Faculty of Science, University of the Witwatersrand Johannesburg, in partial fulfilment of the requirements for the degree of Master Science, 2019